A study of serum albumin levels in acute coronary syndrome and its correlation with clinical outcome - Dhanju, Avtar Singh; Chhina, Gurpreet Singh; Manekar, Praneet; Sandhu, Pashaura Singh (International Journal of Advances in Medicine, 2022)
Background: Coronary artery disease (CAD) is major cause of death and mortality in the developed world. Coronary atherosclerotic disease involves the epicardial coronary arteries and may manifest as an acute or chronic coronary syndrome. Acute coronary syndrome (ACS) arises from atherosclerotic plaque rupture leading to coronary thrombosis and/or spasm. Methods: The present study was conducted in department of medicine, Guru Nanak Dev hospital attached to government medical college, Amritsar from May 2021 to December 2021. This was a prospective observational study in which a total of 50 patients of ACS were enrolled. Serum albumin levels of the patients were recorded and clinical outcomes based on the albumin levels were compared between the patients. Results: The patients with low serum albumin levels had worse outcomes. The mean serum albumin level of STEMI and NSTEMI patients in hypoalbuminemia group was 2.88±0.11 g/dl and 3.15±0.26 g/dl (p=0.047). The mean serum albumin level of patients having mortality in hypoalbuminemia group was 2.87±0.06 g/dl and those who didn’t have mortality was 3.19±0.21 g/dl (p=0.013). The mean serum albumin level of patients developing new onset heart failure in hypoalbuminemia group was 2.85±0.06 g/dl and those not developing had 3.11±0.19 g/dl (p=0.021). Conclusions: We conclude that ACS patients presenting with hypoalbuminemia are more likely to develop worse outcomes in the form of heart failure, cardiogenic shock and mortality. ACS patients presenting with low serum albumin levels have more chances of developing STEMI.